Pengaruh Person-Organizational FIT, Person-job Fit dan Pemberdayaan Guru terhadap Persepsi Guru dalam Memimpin di Sekolah XYZ Jakarta - Manihar Prepto Devit (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2024)
The purpose of this study is to investigate variables that affect teacher leadership. It focused on human resources frame that highlight a good fit between people and organization benefit both parties. Data were collected through questionnaires to 28 teachers teaching from play group level up to 12th grade at XYZ School Jakarta followed by interview to several teachers. Data analysis was carried out by using structural equation modeling with Partial Least Square (PLS) method by utilizing SmartPLS 3.2.7 for Windows. Person-organization fit, Person-job fit and teacher empowerment were found positively affect teacher leadership with path coefficient consecutively +0.366, +0.363, and +0.337. Using teacher empowerment as intervening variables to person-organization fit and person-job fit, their total impact is 76.5% to teacher leadership. Goodness of fit (GoF) produced was 0.629 (large) that indicated model fit in explaining data. Using 95% confidence interval (p=0.05), each human resources factor analyzed was found statistically significant to teacher leadership. The results obtained can be very useful for school leaders to plan and to develop human resource programs that support teacher leaders.